Periodization theory and methodology of training - Bompa, Tudor O.; Buzzichelli, Carlo (Human Kinetics, 2019)
Learn how to maximize training gains with Tudor O. Bompa, the pioneer of periodization training, and Carlo A. Buzzichelli, one of the world's foremost experts on training methods, in the sixth edition of Periodization: Theory and Methodology of Training. Guided by the authors' expertise, the sixth edition offers information central to understanding the latest research and practices related to training theory while providing scientific support for the fundamental principles of periodization.